How 5-fluorouracil acts - Wawrocka-Pawlak, Marlena (Contemporary Oncology/Współczesna Onkologia, 2005)
5-fluorouracil (5-FU) has proved to be one of the most effective chemotherapeutics for colorectal cancer. It is also used as a drug against breast, head and neck, esophageal, gastric, and several other cancers. Intracellular activation is required for the 5-FU to exert its cytotoxic effects. The main active 5-FU metabolites are 5-flouro-2’-deoxiuridine monophosphate (5-FdUMP), 5-flouro-2’-deoxiuridine triphosphate (5-FdUTP), and 5-flourouridine triphosphate (5-FUTP). In the presence of the reduced folate cofactor, 5,10-methylenetetrahydrofolate, 5-FdUMP forms a stable covalent complex with thymidylate synthase (TS). Inhibition of TS leads to depletion of 2’-deoxithymidine triphosphate, thus interfering with DNA biosynthesis and repair. Incorporation of 5-FdUTP into cellular DNA, with resultant inhibition of DNA synthesis and function, may represents another mechanism of cytotoxicity. In addition, 5-FUTP is extensively incorporated into both nuclear and cytoplasmic RNA species, and this process interferes with normal RNA function and protein synthesis. The combined actions of 5-FU metabolites are associated with inhibition of DNA biosynthesis, altered DNA stability, production of DNA damages, and interference with DNA repair. The genotoxic stress resulting from 5-FU administration may activate apoptosis in susceptible cells. The DNA damage checkpoints employ damage sensor proteins, such as ATM, ATR, the MRN complex, and the 9-1-1 complex, to detect DNA damage and to initiate signal transduction cascades that employ Chk1 and Chk2 kinases and Cdc25 phosphatases. The signal transducers activate p53-dependent apoptosis, as well as inactivate cyclin-dependent kinases to inhibit cell cycle progression. Several studies have implicated mitochondria-derived reactive oxygen species in 5-FU-dependent apoptosis.